2007
DOI: 10.1086/511984
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Holoendemic Malaria Results in Suppression of Epstein‐Barr Virus–Specific T Cell Immunosurveillance in Kenyan Children

Abstract: Children living in malaria-holoendemic areas have diminished EBV-specific T cell immunosurveillance between the ages of 5 and 9 years, which coincides with the peak age incidence of eBL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
4
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 43 publications
(52 reference statements)
4
76
4
1
Order By: Relevance
“…A distinct possibility exists for genetic variation that alters the balance between antiinflammatory and proinflammatory cytokines to contribute to the immunologic dysregulation over EBV observed in eBL. [32][33][34] IL-6 and IL-10 are two cytokines that have been implicated in the pathogenesis and progression of other lymphoproliferative disorders. 14,35,36 We hypothesized that these cytokines could potentially provide a permissive milieu for eBL oncogenesis, and therefore, patients with eBL might be more likely to possess genotypes that predispose them to higher levels of inducible IL-6 and IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…A distinct possibility exists for genetic variation that alters the balance between antiinflammatory and proinflammatory cytokines to contribute to the immunologic dysregulation over EBV observed in eBL. [32][33][34] IL-6 and IL-10 are two cytokines that have been implicated in the pathogenesis and progression of other lymphoproliferative disorders. 14,35,36 We hypothesized that these cytokines could potentially provide a permissive milieu for eBL oncogenesis, and therefore, patients with eBL might be more likely to possess genotypes that predispose them to higher levels of inducible IL-6 and IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study revealed a deficiency in IFN-␥ production by EBV-specific CD8 ϩ T cells in children residing in a region with holoendemic malaria (23). However, the events that precede this immune deficiency are unclear.…”
Section: Interestingly Cd8mentioning
confidence: 97%
“…Although these observations suggest that P. falciparum malaria infection disrupts EBV-specific immunity, the effector cells or mediators responsible for controlling EBV-infected B-cell growth were not identified, and overall immune competence was not assessed in the small number of individuals studied. More recently, an age-related deficiency in IFN-␥ recall responses to EBV lytic and latent antigens was demonstrated in children (i.e., 5 to 9 years of age) with ho-loendemic malaria exposure compared to those from an area of malaria hypoendemicity (23). In addition, EBV load in African children correlates with malaria exposure (24,25), further implicating coinfection as a risk factor for eBL tumorigenesis.…”
mentioning
confidence: 99%
“…DNA was extracted from the cells using a Qiagen DNeasy kit (Qiagen) according to the manufacturer's protocol. EBV DNA levels were determined as previously described using primers and probes designed to detect a 70-bp region of the EBV BALF5 gene and the ␤-actin gene as a control for DNA input (25,26).…”
Section: Production Of Ebvmentioning
confidence: 99%